Effect of Oyster Mushroom (Pleurotus Florida) on Paracetamol Induced Changes of serum bilirubin level and liver tissue protein in Rats - Sumy, Afroza Khanam; Jahan, Nasim; Sultana, Nayma; Amin, SM Ruhul (Journal of Bangladesh Society of Physiologist, 2011)
Backgroud: Liver is continuously exposed to a variety of toxic agents like drugs and chemicals that may interfere with hepatic function and may cause hepatic damage. Oyster mushroom is excellently edible, nutritious and has got free radical scavenging activity, thereby may be considered as hepatoprotective agent. Objective: To observe the effect of Oyster mushroom on paracetamol induced changes in serum bilirubin and liver tissue protein in rats. Method: This experimental study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from 1st July 2009 to 30th June 2010. A total number of 34 Wistar albino rats, age ranged from 90 to 120 days, weighing between 150 to 210 grams were selected for the study. After acclimatization for 14 days, they were divided into two groups, control group (Group A) and experimental group (Group B- mushroom pretreated and paracetamol treated group). Control group was again subdivided into group A1 (baseline control) and group A2 (paracetamol treated control group). All groups of animals received basal diet for 30 consecutive days. Group A1 consisted of 10 rats, received propylene glycol (2 ml/kg bw, orally) only on 30th day. Group A2 consisted of 14 rats, received single dose of paracetamol suspension (750 mg/ kg bw, orally) only on 30th day. Group B consisted of 10 rats, received mushroom extract (200 mg/ kg bw, orally) for 30 consecutive days and paracetamol suspension (750 mg/ kg bw, orally) only on 30th day. All the animals were sacrificed on 31st day. Then blood and liver sample were collected. Estimation of serum total bilirubin level and assessment of protein concentration in liver tissue homogenate were done by using standard laboratory kits. The statistical analysis was done by one way ANOVA and Bonferroni test as applicable. Result: The mean serum total bilirubin was significantly (p< 0.001) higher in paracetamol treated group in comparison to that of baseline control group. Again, the mean serum total bilirubin was significantly (p<0.001) lower in mushroom pretreated and paracetamol treated group (experimental group) when compared to that of paracetamol treated group (control). The protein concentration in liver tissue homogenate was significantly (p<0.01) lower in paracetamol treated group in comparison to that of baseline control group. Again, in the liver tissue homogenate protein concentration was significantly (p<0.001) higher in mushroom pretreated and paracetamol treated group (experimental group) when compared to that of paracetamol treated group (control). Conclusion: The present study revealed that Oyster mushroom can protect liver tissue against paracetamol induced liver damage. Key words: Hepatoprotective; Oyster mushroom; Tissue homogenate DOI: http://dx.doi.org/10.3329/jbsp.v6i1.8060 J Bangladesh Soc Physiol. 2011 June; 6(1): 10-15